Cinaciguat prevents neointima formation after arterial injury by decreasing vascular smooth muscle cell migration and proliferation - Hirschberg, Kristóf; Tarcea, Valentin; Mambou Kamdem Gwanmesia, Patricia Neh; Korkmaz-İçöz, Sevil; Radovits, Tamás; Loganathan, Sivakkanan; Karck, Matthias; Szabó, Gábor (International journal of cardiology, 2013)
Aims: Vascular smooth muscle cell (VSMC) migration, proliferation and remodeling of the extracellular matrix contribute to lumen loss after arterial injury leading to restenosis. Several studies indicated the role of the cyclic guanosine monophosphate signaling in neointimal formation. Cinaciguat, the novel soluble guanylate cyclase activator, currently being in phase IIb clinical trial, has been shown to exert antiplatelet and anti-remodeling effects in animal models of vascular pathology. In this study we investigated the effects of cinaciguat on post-injury arterial stenosis. Methods and Results: Male Sprague-Dawley rats (n=100) underwent endothelial denudation by wire injury of the right common carotid artery. Cinaciguat (10mg/kg/day orally) were administered to 50 rats (1-, 2-, 3-day and 1-, 3-week treatment time), while 50 rats received placebo. A 3-week treatment resulted in a significantly reduced vascular stenosis (17.53±10.84% in the treatment group vs. 43.25±30.83% in the control wire injury group) and neointima/media area ratio (0.45±0.32 in the treatment group vs. 1.09±0.69 in the control wire injury group). By using quantitative real-time PCR, Western blot and immunohistochemistry, matrix-metallopreoteinase-9 (MMP-9) was found to be upregulated in the control-injured carotids over the whole follow-up, and cinaciguat significantly decreased MMP-9 expression by 3weeks. As assessed by protein immunoblot, injury-induced local decrease of soluble guanylate cyclase β1 subunit could be recovered by cinaciguat. In vitro wound healing assay with VSMCs revealed dose-dependent antimigratory and antiproliferative effects of cinaciguat. Plasma level of cyclic guanosine monophosphate was significantly elevated after 3weeks of treatment. Conclusion: Our results show that cinaciguat prevents injury-induced neointimal hyperplasia by decreasing VSMC migration and proliferation through the regulation of MMP-9.
Gesehen am 12.07.2018
Available online 20 February 2012